Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.molpharmaceut.8b01250
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Antigen Arrays for Selective Desensitization of Insulin-Reactive B Cells

Abstract: Autoimmune diseases are believed to be highly dependent on loss of immune tolerance to selfantigens. Currently, no treatments have been successful clinically in inducing autoantigen-specific tolerance, including efforts to utilize antigen-specific immunotherapy (ASIT) to selectively correct the aberrant autoimmunity. Soluble antigen arrays (SAgAs) represent a novel autoantigen delivery system composed of a linear polymer, hyaluronic acid (HA), displaying multiple copies of conjugated autoantigen. We have previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 39 publications
(70 reference statements)
1
28
0
Order By: Relevance
“…They demonstrated that these multivalent soluble antigen arrays target antigen-specific B cells directly through binding to the B cell receptor (BCR), rendering the B cell anergic (unresponsive) [ 21 , 23 ]. Using a similar technology to couple insulin to the polymeric background, the same group demonstrated specific binding to insulin-reactive B cells and resulting desensitization [ 24 ]. Though it appears promising, it remains to be seen if targeting insulin-reactive B cells using this method results in protection from disease development.…”
Section: Methods To Target Antigen-specific B Cells: the “How?”mentioning
confidence: 99%
“…They demonstrated that these multivalent soluble antigen arrays target antigen-specific B cells directly through binding to the B cell receptor (BCR), rendering the B cell anergic (unresponsive) [ 21 , 23 ]. Using a similar technology to couple insulin to the polymeric background, the same group demonstrated specific binding to insulin-reactive B cells and resulting desensitization [ 24 ]. Though it appears promising, it remains to be seen if targeting insulin-reactive B cells using this method results in protection from disease development.…”
Section: Methods To Target Antigen-specific B Cells: the “How?”mentioning
confidence: 99%
“…Acetic acid (AA) was identified as an appropriate solvent for PI (Linde et al 1991;Landreh et al 2012) and has been previously used in the MN coating formulations of pancreatic autoantigens (Zhao et al 2016). However, in an acidic environment, acidic amino acids become more protonated, disrupting salt bridges and altering the secondary structure of a protein (Leon et al 2019). The resultant unfolding of the protein exposes hydrophobic residues to the external environment (Choi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The full-length C-peptide was found to be a stronger agonist for C-peptide-specific CD4+ T cell clones than 18-amino acid peptides which incorporated the cognate antigen, eluding to the importance of the presence of multiple epitopes (So et al 2018). An innovative method of ASI has been recently reported which utilizes the insulin protein as the candidate antigen (Leon et al 2019). Soluble antigen array insulin (SAgA Ins ) consist of multiple insulin molecules conjugated to hyaluronic acid and drain from the site of injection to secondary lymphoid organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The autoantigen-targeting approach of mAb123 holds additional functionality beyond Fc recognition: F(ab’)2 123 (which lacks the Fc domain) reinforces central tolerance in the bone marrow via receptor editing to enhance clearance of AIBCs from the repertoire, presumably through enhanced cross-linking of BCRs bound monovalently to insulin [ 81 ] ( Figure 2 ). Soluble antigen arrays, in which insulin is conjugated to polymers, have also been used to reinforce immune tolerance in AIBCs [ 82 ].…”
Section: Therapeutic Targeting Of Aibcsmentioning
confidence: 99%